Dampak Disrupsi Digital terhadap Beban Kerja dan Produktivitas Tenaga Pelayanan Publik di Disdukcapil Kota Serang - Jesika Sulastri; Kenedi Kenedi (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2026)
Digital transformation in public services has become an essential strategy for governments to improve the quality, effectiveness, and efficiency of service delivery to the community. The Department of Population and Civil Registration (Disdukcapil) of Serang City has implemented a digital service innovation through the Smartdukcapil application to facilitate public access to various population administration services. However, in practice, several obstacles are still encountered, particularly the limited public understanding of digital service procedures and the use of the application. As a result, many citizens continue to visit service counters directly, indicating that the objectives of service digitalization have not been fully achieved. This community service activity aims to enhance public understanding and digital literacy regarding the use of the Smartdukcapil application and online population administration procedures. The methods employed in this activity include field observation, digital service socialization, and direct assistance to community members in managing population administration documents. The activity was conducted for one month at the Department of Population and Civil Registration of Serang City, involving service users and frontline staff as partners in the program. The results show that the socialization and assistance activities improved community understanding of digital service mechanisms and helped reduce errors in fulfilling administrative requirements. Furthermore, this activity contributed to improving the effectiveness of public service delivery and supporting the implementation of digital-based population administration services. Therefore, this community service initiative is expected to enhance community digital literacy and support the optimization of technology-based public services.